Use of radiotelemetry to quantify diel habitat preferences and minimum environmental flow requirements of a tropical riverine fish (Sooty grunter Hephaestus fuliginosus). Issue 5 (24th March 2021) - Crook, David A.; Keller, Krystle; Adair, Brendan J.; Luiz, Osmar J.; Waugh, Peter S.; Schult, Julia; Dostine, Peter L.; Townsend, Simon A.; King, Alison J.
Abstract: Quantitative relationships between river discharge and hydraulic habitat availability for key taxa are important elements of environmental flow assessment. We used radiotelemetry to examine diel patterns of habitat use by tracking the locations of 17 juvenile Sooty grunter ( Hephaestus fuliginosus ) over a 10‐day period during the late dry season in a river in the wet–dry tropics of northern Australia. Habitat use data were integrated with a hydrodynamic model to identify preferred hydraulic habitat and explore different river discharge scenarios to assess the potential effects of water abstraction on habitat availability. Sooty grunter exhibited a strong preference for shallow, fast flowing mesohabitat (riffles and runs). Hydraulic microhabitat preference was modelled using generalised additive mixed‐effect models (GAMMs) and showed no significant difference in microhabitat selection between day and night. Habitat criteria developed from a combined day‐night GAMM were defined as locations with velocities of 0.26–1.42 m s −1 and depths <0.69 m. Hydrodynamic modelling of river discharge scenarios in the study reach showed that the area of preferred habitat was highest at 8 m 3 s −1, with large declines in habitat area under low flows (61% decline in habitat area at 0.5 m 3 s −1 compared to the discharge of 2.8 m 3 s −1 at the time of radio‐tracking). While the study focusses on a single species, our findings demonstrate the broad applicability of radiotelemetry as a means of quantifying the diel hydraulic habitat requirements of riverine fish to support the objective determination of environmental flow regimes.